Continuous training for teachers in culinary and gastronomy programs in Peru - Quea-Campos, Mariel R. (2024)
The article proposes a review of scientific publications regarding the increase in cooking and gastronomy schools in Peru and the academic needs of teachers, based on the country's positioning as one of the destinations with the best gastronomy in the world. In recent years, technology has made it possible to publish scientific articles and scientific journals specialized in different topics, among which gastronomy and teacher training also have a place, therefore, for people or institutions linked to the field. can access it without difficulty, the systematization of the information that is accessible in the digital space is necessary. To this end, a systematic review has been carried out based on the PRISMA Methodology “Preferred Reporting Elements for Systematic Reviews and Meta-Analyses” (for its acronym in English) to identify relevant information regarding: What is the incidence of continuing training? in the performance of teachers in gastronomy careers?, a methodology that allows a systematic review of content that provides information with effective levels of trust and credibility. We worked with the metasearch engines SciELO, Google Scholar, Scopus and Redalyc and, as a final result, 35 scientific articles were found that met the requirements established as search criteria. The research includes the analysis of the academic and pedagogical needs of teachers, for adequate performance in the training of cooking and gastronomy students.